2019
DOI: 10.1182/blood.2019000909
|View full text |Cite
|
Sign up to set email alerts
|

Germline DDX41 mutations define a significant entity within adult MDS/AML patients

Abstract: This report presents the intriguing observation that cases with germline DEAD-box helicase 41 (DDX41) mutations represent a unique entity among adult myeloid neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
141
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(193 citation statements)
references
References 19 publications
(25 reference statements)
19
141
1
4
Order By: Relevance
“…While it is possible that the genetic properties of this mutation might differ between C. elegans and mammalian systems, it is worthwhile noting that the oncogenic variant must support the high levels of proliferation characteristic of neoplastic cells. While all the sacy-1 mutations we isolated in forward genetic screens occur at conserved amino acids, none of them match the oncogenic mutations thus far isolated (Polprasert et al 2015;Cardoso et al 2016;Lewinsohn et al 2016;Li et al 2016;Diness et al 2018 ;Sébert et al 2019). This observation is consistent with the idea that the oncogenic mutations are at most weakly antagonizing or weak reduction-of-function mutations, and thus would not have been isolated in forward genetic screens that require a substantial reduction in function.…”
Section: Discussionmentioning
confidence: 91%
“…While it is possible that the genetic properties of this mutation might differ between C. elegans and mammalian systems, it is worthwhile noting that the oncogenic variant must support the high levels of proliferation characteristic of neoplastic cells. While all the sacy-1 mutations we isolated in forward genetic screens occur at conserved amino acids, none of them match the oncogenic mutations thus far isolated (Polprasert et al 2015;Cardoso et al 2016;Lewinsohn et al 2016;Li et al 2016;Diness et al 2018 ;Sébert et al 2019). This observation is consistent with the idea that the oncogenic mutations are at most weakly antagonizing or weak reduction-of-function mutations, and thus would not have been isolated in forward genetic screens that require a substantial reduction in function.…”
Section: Discussionmentioning
confidence: 91%
“…Patients with myeloid neoplasms with DDX41 mutations were initially reported to have a poor prognosis but this analysis included both germline and somatic mutations, including patients with 5q deletions spanning the DDX41 locus . In contrast, a recent study including only patients with germline mutations showed no significant difference in survival …”
Section: Myeloid Neoplasms With Germline Predisposition Without a Prementioning
confidence: 99%
“…Com mais de 70 famílias já descritas, vem se tornando uma das propensões germinativas mais descritas 31 . Dois grandes estudos em populações não selecionadas de LMA e SMD identificaram presença da mutação, provavelmente, germinativa em quase 2,5% dos casos, fazendo com que esta seja provavelmente a NMPG mais comum 32,33 . Ela difere das demais propensões familiares pelo tempo de latência maior e mediana de idade ao diagnóstico em torno de 70 anos 32,33 .…”
Section: Neoplasia Mieloide Com Mutação Germinativa De Ddx41unclassified
“…Dois grandes estudos em populações não selecionadas de LMA e SMD identificaram presença da mutação, provavelmente, germinativa em quase 2,5% dos casos, fazendo com que esta seja provavelmente a NMPG mais comum 32,33 . Ela difere das demais propensões familiares pelo tempo de latência maior e mediana de idade ao diagnóstico em torno de 70 anos 32,33 . O tipo de mutação pode sugerir a origem germinativa, uma vez que até o momento não foram encontradas mutações do tipo frameshift somaticamente 32,34 .…”
Section: Neoplasia Mieloide Com Mutação Germinativa De Ddx41unclassified
See 1 more Smart Citation